Edukasi Metode Demonstrasi dan Jigsaw untuk Meningkatkan Kemampuan Pertolongan Pertama Syncope - Nurul Laili; Linda Ishariani; Farida Hayati; Ayu Wandari Samad (Yayasan Inspirasi El Burhani, 2026)
Introduction: Syncope is a common occurrence in schools, especially among adolescents. First aid skills are crucial in health education, particularly in dealing with emergencies like syncope. Education and training in syncope first aid are needed to ensure students are better prepared and capable of handling emergency situations. One way to improve syncope first aid skills is through interactive demonstration and jigsaw learning methods. Objective: The aim of this community service activity is to provide knowledge and skills through education using demonstration and jigsaw methods regarding the management of syncope in adolescents in the school environment. Method: The activity was implemented through demonstration and jigsaw education. The activity was held for four days, from September 6-9, 2025, at SMPN 3 Kertosono. Participants were 20 students of SMPN 3 Kertosono. Result: The pre-test evaluation results, before being given education, showed that the majority (65%) of respondents were in the adequate category in their syncope first aid skills. The post-test results, after being given education, showed that all (100%) achieved the good category in their syncope first aid skills. Conclusion: Visual and auditory stimuli from demonstrations and jigsaw discussions are processed by the brain into understanding and skills. Repeated observation and practice strengthen motor memory, improving students' overall abilities. This method can enhance students' ability to handle syncope. It is recommended that this method be applied continuously in student learning to optimally improve abilities.